O consumo de bens culturais na era da internet: práticas e usos da cultura entre estudantes do ensino médio em Realeza/ PR - Tonkelski, Camila Cararo (2017)
The dissertation has the propose to understand that way the young relation it with certain symbolic goods at a time when they are enjoyed in large extent with the resource of digital devices and by means of the Internet. The research was realized between the young students of high school in Realeza/PR. The objective is to identify differences in methods of cultural enjoyment, offered by those technologies, between young of distinct social, economic, and cultural conditions. It is seeking to analyze the young choose the activities, products and information that on this network.